UCDP External Support Data - UCDP External Support – Disaggregated/Supporter Dataset - Högbladh, Stina; Pettersson, Therése; Themnér, Lotta (Uppsala University, 2015)
The UCDP, Uppsala Conflict Data Program, contains information on a large number data on organised violence, armed violence, and peacemaking. There is information from 1946 up to today, and the datasets are updated continuously. The data can be downloaded for free, and available in several different versions.

The UCDP External Support Data contains information of external support in intrastate conflicts, 1975-2010. Provides information of kind of support, extern actor and specific year. The data is divided into two separate datasets which are analogous, i.e. contain identical data structured in a different manner to simplify various types of research such as different types of statistical analyses.

Purpose:

The Uppsala Conflict Data Program (UCDP) collects information on a large number of aspects of armed violence since 1946.

The dataset provide data where the unit of analysis is the warring party-supporter-year, i.e. each row in the dataset contains information on the type of support that a warring party receives from a specific external party in a given year, using dummy variables for each category of support. The dataset contains information for the time-period 1975–2010.

UCDP, Uppsala Conflict Data Program vid Uppsala universitet, innehåller stora mängder data över organiserat våld, väpnade konflikter och fredsarbete. Idag täcker UCDP´s data över hela världen, från 1946 och framåt, och finns presenterade i 13 olika dataset som kontinuerligt uppdateras. Datan finns tillgänglig för gratis nedladdning och användning via UCDP´s hemsida.

UCDP External Support Data innehåller information om externt stöd i inomstatliga konflikter, mellan åren 1975-2010. Datan beskriver vad för typ av stöd, från vilken aktör och vilka specifika år det gavs. Datan finns i två olika dataset som är identiska avseende innehåll men har strukturerats på olika sätt.

Syfte:

Syftet för UCDP är att samla olika typer av information om väpnade konflikter från hela världen, från 1946 fram till idag.

Ett dataset som ger data över vilken typ av stöd en krigsförande aktör får från en specifik extern part under ett visst år, med dmmy-varibler för varje kategori av stöd. Datasetet täcker tidsperioden 1975-2010.
UCDP External Support Data - UCDP External Support – Disaggregated/Supporter Dataset
Keywords: internal political conflict; inrikespolitiska konflikter; peace; fred; conflict; konflikt; political support; politiskt stöd; civil war; inbördeskrig; armed forces; väpnade styrkor; grants; stöd; state aid; statligt stöd; guerrilla activities; gerillaaktivitet; assault; våld; Conflict, security and peace; Konflikter, säkerhet och fred; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap